Association of the GALNTL6 rs558129 polymorphism with muscle strength in Japanese athletes - Kozuma, Ayumu; Miyamoto-Mikami, Eri; Saito, Mika; Homma, Hiroki; Deguchi, Minoru; Matsumoto, Shingo; Matsumoto, Ryutaro; Okamoto, Takanobu; Nakazato, Koichi; Fuku, Noriyuki; Kikuchi, Naoki (Biology of Sport, 2025)
The significance of GALNTL6 rs558129 polymorphism in relation to muscle strength and power performance has been reported in several studies. However, there has been no replication study in the Japanese population. Therefore, in this study, we aimed to determine the association of GALNTL6 rs558129 polymorphism with athlete status and muscle strength in Japanese athletes. In study 1, genotype frequencies were compared between 376 power-oriented athletes (male: n = 257, female: n = 119) and 1,139 controls (male: n = 448, female: n = 691). The power-oriented athletes included wrestlers ( n = 146), weightlifters ( n = 151) and power lifters ( n = 79). In study 2, isokinetic knee extension and flexion muscle strength tests were performed in 347 athletes (male: n = 298, female: n = 49). In both studies, GALNTL6 rs558129 polymorphism was identified using the TaqMan SNP Genotyping Assay. In study 1, there were no significant differences in genotype frequencies between the power-oriented athletes and controls. However, the frequency of TT genotype was significantly higher in wrestlers compared to controls ( p = 0.044). In study 2, isokinetic knee extension muscle strength was significantly higher in athletes with the T allele than in athletes with the CC genotype ( p = 0.012). In addition, a significant tendency of the isokinetic knee extension muscle strength was observed in the CC, CT, and TT genotype, respectively. The results of this study suggest that the TT genotype and T allele of GALNTL6 polymorphism are associated with knee extension muscle strength in Japanese athletes and that the TT genotype is observed at a higher frequency in Japanese wrestlers. These findings are consistent with and further validate the results of previous studies.